Parental leave and mothers' careers: The relative importance of job protection and cash benefits - Rafael Lalive; Analia Schlosser; Andreas Steinhauer; Josef Zweimüller (Institute for the Study of Labor (IZA), 2011)
Parental leave regulations in most OECD countries have two key policy instruments: job protection and cash benefits. This paper studies how mothers' return to work behavior and labor market outcomes are affected by alternative mixes of these key policy parameters. Exploiting a series of major parental leave policy changes in Austria, we find that longer cash benefits lead to a significant delay in return to work and that the magnitude of this effect depends on the relative length of job protection and cash benefits. However, despite their impact on time on leave, we do not find a significant effect on mothers' labor market outcomes in the medium run, neither of benefit duration nor of job-protection duration. To understand the relative importance (and interaction) of the two policy instruments in shaping mothers' return to work behavior, we set up a non-stationary job search model in which cash benefits and job protection determine decisions of when to return to work and whether or not to return to the pre-birth employer. Despite its lean structure, the model does surprisingly well in matching empirically observed return to work profiles. The simulation of alternative counterfactual regimes shows that a policy that combines both job protection and benefits payments succeeds to induce mothers to spend some time with the child after birth without jeopardizing their medium run labor market attachment.
urn:nbn:de:101:1-201106224739
Keywords: J13; J18; J22; 330; parental leave; family and work obligations; return to work; labor supply; earnings; family earnings gap